Ze studiów nad malarskim wystrojem kościoła parafialnego w Kraśniku (dzieła Tomasza Dolabelli i Jana Kasińskiego) - Żmudziński, Jerzy (Archiwa, Biblioteki i Muzea Kościelne, 2018)
The following article discusses the paintings of the former Canons Regular church in Kraśnik. The analysis results in the conclusion that the church interior reflects the particular activity of the then-hosts of the church – the Zamoyski family – during the period in which the town and the church held a significant position. The paintings (over 15), done in the studios of two painters: Tomasz Dolabella and Jan Kasiński in the years 1626-1631, are an example of the influence of Venetian paintings developing at the turn of the 17th century; at the same time, they constitute the effective implementation of the reform recommendations made by the Council of Trent.